Perancangan Sistem Informasi Surat Keterangan Pendamping Ijazah pada Politeknik Negeri Padang - ni, def; Fadly, Fathur Ridha (Jurnal Momentum ISSN 1693-752X)
Surat Keterangan Pendamping Ijazah (SKPI) is a companion certificate given to students to accompany diplomas and transcripts. SKPI is a certificate explaining the additional identity of the certificate holder.at the State Polytechnic, the making of SKPI is still done manually.This study aims to make SKPI using applications made using Laravel and MySQL databases.This research will produce SKPI reports given to alumni